2020
DOI: 10.13057/biodiv/d210922
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: The effect of water quality on the population density of Pterygoplichthys pardalis in the Ciliwung River, Jakarta, Indonesia

Abstract: Abstract. Elfidasari D, Wijayanti F, Muthmainah HF. 2020. Short Communication: The effect of water quality on the population density of Pterygoplichthys pardalis in the Ciliwung River, Jakarta, Indonesia. Biodiversitas 21: 4100-4106. The quality of waters is determined by the average value of the measured parameter range with a direct impact on aquatic biota due to pollution. The Ciliwung River is one of the polluted waters in Jakarta, which is the habitat for Pterygoplichthys pardalis (plecos catfish) that do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For example, sailfin catfish have been speculated to impact aquatic plant species due to their grazing habits (Hussan et al, 2019), and contribute towards bank erosion in Marikina river, Philippines, as they burrow during the breeding seasons (Jumawan & Herrera, 2014;Hoover et al, 2014). Elfidasari et al, (2020) experimentally showed that post introduction of the Amazon sailfin catfish, at Ciliwung river, Jakarta, Indonesia, the water was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…For example, sailfin catfish have been speculated to impact aquatic plant species due to their grazing habits (Hussan et al, 2019), and contribute towards bank erosion in Marikina river, Philippines, as they burrow during the breeding seasons (Jumawan & Herrera, 2014;Hoover et al, 2014). Elfidasari et al, (2020) experimentally showed that post introduction of the Amazon sailfin catfish, at Ciliwung river, Jakarta, Indonesia, the water was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…He's not a fan of doing hard work, but he's pretty good at making plans. These are interpretation of characteristics that can be found in common catfishes which is stereotyped as one of the low maintenance livestocks where they are often found in waste disposal, murky rivers or ponds as mentioned by Elfidasari [9].…”
Section: Discussionmentioning
confidence: 99%
“…This fish can take the oxygen from the water's surface when the water's oxygen concentration is in low condition. Moreover, this fish is also adaptable in high-pollution environments [24].…”
Section: Table 2 Environmental Parameters In Situ Cikaret and Situ Ci...mentioning
confidence: 99%